Teens and jeans : clothing in transition - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
Denim and jeans are consistently popular in most countries throughout the world. However, despite their universal appeal, different markets result in different brands and denim styles being more popular in some countries than others. This case study examines the international jeans market, particularly among teenagers.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Teens and Jeans: Clothing in Transition. In International marketing (pp. 37-38). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Jeans (Clothing) -- Case studies; Consumers' preferences -- Case studies; Teenage consumers -- Case studies